2018
DOI: 10.1007/s12035-018-0872-8
|View full text |Cite
|
Sign up to set email alerts
|

Mesencephalic Astrocyte-Derived Neurotrophic Factor (MANF) Elevates Stimulus-Evoked Release of Dopamine in Freely-Moving Rats

Abstract: Neurotrophic factors (NTFs) hold potential as disease-modifying therapies for neurodegenerative disorders like Parkinson’s disease. Glial cell line-derived neurotrophic factor (GDNF), cerebral dopamine neurotrophic factor (CDNF), and mesencephalic astrocyte-derived neurotrophic factor (MANF) have shown neuroprotective and restorative effects on nigral dopaminergic neurons in various animal models of Parkinson’s disease. To date, however, their effects on brain neurochemistry have not been compared using in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Further research on the exact mechanisms of α-syn clearance will help understand the neuroprotective role of IRE1. Mesencephalic astrocyte-derived neurotrophic factor (MANF), also known as ARMET (arginine-rich mutated in early-stage tumors) is present in ER and promotes neuronal cell survival through UPR regulation (Apostolou et al, 2008;Renko et al, 2018;Wang et al, 2021). ER stress triggers the accumulation of misfolded α-syn (Colla et al, 2012a).…”
Section: Mechanism Of Neuronal Clearance Of Misfolded α-Synuclein By Autophagymentioning
confidence: 99%
“…Further research on the exact mechanisms of α-syn clearance will help understand the neuroprotective role of IRE1. Mesencephalic astrocyte-derived neurotrophic factor (MANF), also known as ARMET (arginine-rich mutated in early-stage tumors) is present in ER and promotes neuronal cell survival through UPR regulation (Apostolou et al, 2008;Renko et al, 2018;Wang et al, 2021). ER stress triggers the accumulation of misfolded α-syn (Colla et al, 2012a).…”
Section: Mechanism Of Neuronal Clearance Of Misfolded α-Synuclein By Autophagymentioning
confidence: 99%
“…Consistent with our findings, among the 26 proteins significantly influenced by VB, we identified MANF, an ER stress response protein. As a member of the fourth family of neurotrophic factors, MANF has been proven to protect and repair dopaminergic neurons and maintain the homeostasis of ER proteins [42,43]. According to our STRING protein interaction mapping analysis, MANF is found to interact with ATF4, XBP1, and ATF6.…”
Section: Discussionmentioning
confidence: 94%
“…4 f). MANF is a key factor in alleviating ER stress and maintaining ER homeostasis [ 42 ] and has been confirmed to be upregulated during ER stress and can resist Aβ toxicity by attenuating Aβ-induced ER stress [ 43 ]. In the hippocampus of APP/PS1 mice, VB decreased the expression levels of MANF, suggesting that VB protected against ER stress (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a rat model of Parkinson's disease, MANF can protect rat's tyrosine hydroxylase-positive cells against 6-OHDA induced damage [37], another in vitro studies results suggested that MANF exert neuroprotective role in SH-SY5Y cells after damaged by 6-OHDA [9,38]. Moreover, a recent study indicated that MANF promoted the secretion of dopamine under the injection of MANF into rat striatum [39]. Therefore, it may imply that the potential therapeutic role of MANF in Parkinson's disease.…”
Section: Cytoprotective Role Of Manfmentioning
confidence: 97%